2011
DOI: 10.4314/jasem.v14i4.63287
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Specific Surface Area using Langmuir Isotherm Method

Abstract: A comparison of four widely used linear equations of the Langmuir types of isotherm (The Langmuir Type 1, 2, 3 and 4) were examined in an experiment using dye sorption onto derived acid and salt treated Fish Activated Carbon (H3PO4-FAC and ZnCl2-FAC respectively). Isotherm parameters obtained from the four Langmuir linear equations differed. Though Langmuir type 1 is the most popular form, but the type 2 had the highest coefficient of determination (R 2 = 0.931-0.984) compared with the other Langmuir linear eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 4 publications
0
34
1
1
Order By: Relevance
“…But from Fig-15, it was evident that the line in the initial stage does not pass through the origin instead it depicts two linear portions; the first part of the curve is due to boundary layer diffusion whereas the last part of the curve is due to the diffusion of Pb 2+ ions [57,58]. Table 5.…”
Section: Intraparticle Diffusionmentioning
confidence: 99%
“…But from Fig-15, it was evident that the line in the initial stage does not pass through the origin instead it depicts two linear portions; the first part of the curve is due to boundary layer diffusion whereas the last part of the curve is due to the diffusion of Pb 2+ ions [57,58]. Table 5.…”
Section: Intraparticle Diffusionmentioning
confidence: 99%
“…For example, in a study of the sorptive capacity of granular activated carbon using the cationic dye methylene blue, the authors observed that sorption was directly proportional to the dosage of size-fractionated carbon [24]. Additionally, methylene blue and several other dyes exhibit Langmuir sorption characteristics similar to our observed sorption of denatonium ions onto powdered activated carbon (Figure 4) [26]- [28]. Sorption of organic molecules or ions to highsurface area sorbents can be influenced by number of solution conditions including pH, ionic strength, temperature, nature of background electrolyte, etcetera [29] [30].…”
Section: Discussionmentioning
confidence: 49%
“…Penentuan gliserol total dilakukan berdasarkan metode FBI-A02-03 (FBI, 2006a (Itodo, Itodo, & Gafar, 2010). Sisa metilen biru yang tidak teradsorbsi ditentukan dengan spektrofotometer UV Vis pada panjang gelombang 664 nm.…”
Section: Penentuan Gliserol Totalunclassified